Metaphor in the Song Lyrics of Aurora’s Album: A Different Kind of Human Step 2 - Muhammad Haziq Alwie Danial; Wiwin Widyawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Metaphors are essential for understanding complex ideas and enhancing creativity. Thoroughly studying metaphors reveals their deeper meanings, especially in poetic devices used in songs. Artist Aurora is known for her inspiring and introspective lyrics, particularly in her album